Loneliness as a difficult situation – Overcoming the burden of isolation (Difficult situation in biographies: Volume 9, 2025)
The author attempts an empirical verification of the thesis that loneliness is a difficult situation. She adopts a broad understanding of solitude/loneliness as a universal phenomenon of human existence, paying attention to its negative form, referred to as “isolation,” and its positive form, called “solitude.” She defines the markers of a difficult situation, particularly focusing on its subjective nature, the experience of negative emotions, and engagement in coping activities. Based on her own empirical research, conducted in 2022 using a mixed-methods approach with a sample of 40 adults of various ages, both women and men, she describes loneliness as a complex human experience. One of its most pronounced manifestations is isolation, which is often associated with intense negative emotions experienced over a prolonged, sometimes continuous, period. This state results from a lack or disturbance in relationships with others, especially close ones. The personal aspect of isolation is also linked to social and cultural dimensions. Participants in the study adopt diverse behaviors in response to the experience of isolation. These include strategies such as coping with isolation, accepting and choosing solitude, and transforming isolation into positive solitude. Loneliness, experienced as isolation, is therefore a difficult situation in light of these findings; it is characterized by overload, obstacles, threat, deprivation, crisis, and pathologic. However, it is important to emphasize the widespread efforts aimed at dealing with isolation. A particular manifestation of this is the acceptance of isolation—the choice of solitude and the transformation of isolation into positive solitude. The research results support the thesis of the ambivalent and subjective nature of loneliness, as well as the possibility for an individual, through conscious self-awareness, to shape this experience. Providing extensive knowledge about the complex phenomenon of loneliness is a key task in pedagogical monoseology.